Dysregulation Serum miR-19a-3p is a Diagnostic Biomarker for Asymptomatic Carotid Artery Stenosis and a Promising Predictor of Cerebral Ischemia Events - Xiaoliang Liu MMed; Xiaojun Zheng MMed; Ying Wang MMed; Juan Liu MMed (Clinical and Applied Thrombosis/Hemostasis, 2021)
This study aims to identify the diagnostic potential of microRNA-19a-3p (miR-19a-3p) for asymptomatic carotid artery stenosis (CAS) and clinical predictive potential for cerebral ischemia events (CIEs). Serum samples from 101 asymptomatic CAS patients and 98 healthy controls were collected. And it was found that serum miR-19a-3p in asymptomatic CAS patients was generally elevated ( P  < .05). Increased miR-19a-3p in asymptomatic CAS was associated with severe CAS (odds ratio  = 3.920, 95% confidence interval [CI] = 1.482-10.372, P  < .01). The area under the receiver operating characteristic (ROC) curve (AUC) was 0.905, indicating that the level of miR-19a-3p was statistically significant for the diagnosis of asymptomatic CAS. Furthermore, the level of serum miR-19a-3p (hazard ratio [HR] = 8.507, 95% confidence interval [CI] = 2.239-32.328, P  = .002) and degree of artery stenosis (HR = 3.695, 95% CI = 1.127-12.109, P  = .031) were independent predictors of occurrence of CIE. Moreover, patients with elevated miR-19a-3p levels were more likely to experience CIE than patients with low levels. Upregulated miR-19a-3p can be used as a diagnostic biomarker for asymptomatic CAS patients and as an independent predictor of CIE.